2013
DOI: 10.1016/j.neuroimage.2013.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted cortico-cerebellar connectivity in older adults

Abstract: Healthy aging is marked by declines in a variety of cognitive and motor abilities. A better understanding of the aging brain may aid in elucidating the neural substrates of these behavioral effects. Investigations of resting state functional brain connectivity have provided insights into pathology, and to some degree, healthy aging. Given the role of the cerebellum in both motor and cognitive behaviors, as well as its known volumetric declines with age, investigating cerebellar networks may shed light on the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
108
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 104 publications
(137 citation statements)
references
References 68 publications
12
108
0
Order By: Relevance
“…A role for the cerebellum in both cognitive and motor behavior has been postulated for quite some time (Leiner et al, 1993, 1989, 1986; Schmahmann and Sherman, 1998); moreover, recent work in non-human primates has demonstrated segregated cognitive and motor cerebello-cortical closed-loop circuits (Kelly and Strick 2003; Dum and Strick 2009; for a review see Strick et al 2009). Similar distinct circuits have also been demonstrated in the human brain using fcMRI (Bernard et al, 2012; Bernard et al, 2013; Habas et al, 2009; Krienen and Buckner, 2009; O'Reilly et al, 2010), and crucially, a functional topography has been demonstrated in the cerebellum with fMRI and meta-analysis (Stoodley and Schmahmann, 2010, 2009; Stoodley et al, 2012). Together, this work underscores the importance of investigations of cerebellar sub-regions, as aging may differentially impact regions of the cerebellum associated with cognitive and motor function, and indeed some work has begun to address this question.…”
Section: Cerebellar Morphology In Agingsupporting
confidence: 56%
See 4 more Smart Citations
“…A role for the cerebellum in both cognitive and motor behavior has been postulated for quite some time (Leiner et al, 1993, 1989, 1986; Schmahmann and Sherman, 1998); moreover, recent work in non-human primates has demonstrated segregated cognitive and motor cerebello-cortical closed-loop circuits (Kelly and Strick 2003; Dum and Strick 2009; for a review see Strick et al 2009). Similar distinct circuits have also been demonstrated in the human brain using fcMRI (Bernard et al, 2012; Bernard et al, 2013; Habas et al, 2009; Krienen and Buckner, 2009; O'Reilly et al, 2010), and crucially, a functional topography has been demonstrated in the cerebellum with fMRI and meta-analysis (Stoodley and Schmahmann, 2010, 2009; Stoodley et al, 2012). Together, this work underscores the importance of investigations of cerebellar sub-regions, as aging may differentially impact regions of the cerebellum associated with cognitive and motor function, and indeed some work has begun to address this question.…”
Section: Cerebellar Morphology In Agingsupporting
confidence: 56%
“…A complete overview of the findings of studies investigating connectivity in aging is beyond the scope of this review, and it has recently been reviewed elsewhere (Ferreira and Busatto, 2013). However, the utility of fcMRI to better understand the aging brain is clear, though there has been relatively little work to date investigating cerebello-cortical networks, with the exception of one study (Bernard et al, 2013). With that said, some of the work investigating resting state networks in the aging brain has implicated the cerebellum.…”
Section: Functional Investigations Of the Aging Cerebellummentioning
confidence: 99%
See 3 more Smart Citations